A wireless approach for personal healthcare on everyday mobile devices. (20th February 2012) - Zhou, Helen; Roberts, Tim
This paper presents a wireless approach to remotely monitor physiological signs for mobile users through wireless and mobile networks. A microcontroller–based personal health monitoring unit has been prototyped as a platform for medical sensors and positioning sensors. The unit has been Bluetooth enabled and can pair up with a Bluetooth mobile phone for local health monitoring. Moreover, the mobile phone has been developed as a gateway to further relay these health datasets to a remote database via mobile networks for remote diagnoses. Any medical instructions can be sent back instantly to the mobile users. The use of standard development tools makes it possible for patients to easily use everyday mobile devices for their personal health monitoring and assessment anytime anywhere.